IOS sensor apps with Arduino - Allan, Alasdair (O'Reilly, 2011)
"Learn how to connect the Arduino platform to any iOS device; build a simple application to control your Arduino directly from an iPad; gather measurements from an ultrasonic range finder and display them on your iPhone; connect an iPhone, iPad, or iPod Touch to an XBee radio network; explore other methods for connecting external sensors to iOS, including Ethernet and the MIDI protocol"--Provided by publisher.
Print version record
Keywords: Arduino; iOS (Electronic resource); Application software -- Development; Microcontrollers -- Programming; Programmable controllers; iPhone (Smartphone) -- Programming; iPad (Computer) -- Programming; IOS (Electronic resource); Logiciels d'application; Développement; Microcontrôleurs; Programmation; Automates programmables; iPhone (Téléphone intelligent); Programmation; iPad (Ordinateur); Programmation; COMPUTERS; Programming; General; Application software; Development; Microcontrollers; Programming